2021
DOI: 10.3389/fmed.2021.681621
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and Differences Between Juvenile and Adult Spondyloarthropathies

Abstract: Spondyloarthritis (SpA) encompasses a broad spectrum of conditions occurring from childhood to middle age. Key features of SpA include axial and peripheral arthritis, enthesitis, extra-articular manifestations, and a strong association with HLA-B27. These features are common across the ages but there are important differences between juvenile and adult onset disease. Juvenile SpA predominantly affects the peripheral joints and the incidence of axial arthritis increases with age. Enthesitis is important in earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 232 publications
0
3
0
Order By: Relevance
“…JIA categories are complex, heterogeneous, with different contributions of immune system players and effector cells ( 24 , 25 , 58 63 ). Indeed, several studies have demonstrated a predominance of adaptive immunity in the pathogenesis of oJIA, pJIA, ERA, and JPsA ( 14 , 17 , 18 , 24 , 25 , 39 , 57 , 64 – 86 ), whereas innate immune responses are the major contributors to disease development and progression in sJIA ( 29 , 59 , 87 98 ). In fact, oJIA, pJIA, ERA, and JPsA are classified as autoimmune diseases, while sJIA has been proposed as an autoinflammatory disorder ( 25 , 58 , 59 ).…”
Section: Immunopathogenesis Of Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…JIA categories are complex, heterogeneous, with different contributions of immune system players and effector cells ( 24 , 25 , 58 63 ). Indeed, several studies have demonstrated a predominance of adaptive immunity in the pathogenesis of oJIA, pJIA, ERA, and JPsA ( 14 , 17 , 18 , 24 , 25 , 39 , 57 , 64 – 86 ), whereas innate immune responses are the major contributors to disease development and progression in sJIA ( 29 , 59 , 87 98 ). In fact, oJIA, pJIA, ERA, and JPsA are classified as autoimmune diseases, while sJIA has been proposed as an autoinflammatory disorder ( 25 , 58 , 59 ).…”
Section: Immunopathogenesis Of Juvenile Idiopathic Arthritismentioning
confidence: 99%
“…We compared ERA and juvenile-onset SpA patients due to similarities in clinical features (24). SpA comprises a wide spectrum of clinical and muscle-skeletal features, evolving to spinal involvement with back pain; this is less frequent in ERA, where arthritis and enthesis are predominant features and spine involvement is more frequently seen in adolescents and youngsters (25); such differences could be possibly related to muscle-skeletal development stage, immune response, and the gut microbiota, beyond genetic and other environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…It’s a chronic inflammatory disease characterized by enthesitis, peripheral arthritis predominantly in the lower limbs and axial arthritis (sacroiliitis and spondylitis) which can progress to ankylosing spondylitis at an advanced stage, occurring before 18 years [ 1 , 2 ]. It is distinguished by male predominance, a strong association with HLA-B27 and the development of anterior uveitis [ 3 ]. ERA represents a continuum with adult spondyloarthritis (SpA) and children with HLA-B27-positive ERA are associated with a prolonged disease course and higher incidence of anterior uveitis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%